Compact antenna element for high‐resolution SAR polarimetry applications. Issue 25 (1st December 2013) - Jun, Jiao Jun; Feng, Sun Hui; Kai, Deng Yun; Xue, Jia Xiao
Abstract : For high‐resolution synthetic aperture radar polarimetry applications, a compact broadband dual‐polarised antenna element with high port isolation and low cross‐polarisation is investigated. The size of the element is 19 × 19 × 40 mm, which is much smaller than the traditional dual‐polarised horn. The measured results show that the operating frequencies of both the ports are used from 8.2 to 11.0 GHz, about 30% centred about 9.6 GHz, the port isolation level is below −40 dB and the cross‐polarisation is below −35 dB. The radiation patterns and the gain of the element are presented.